S53 Marked small airway dysfunction and consequent air-trapping characterise chronic hypersensitivity pneumonitis (chp) but not idiopathic pulmonary fibrosis (ipf). (15th November 2017) - Bonini, M; Usmani, O; Pacini, A; Menichini, I; Ward, S; Walsh, S; Daccord, C; Minelli, C; Brunori, M; Wells, AU; Chua, F
Abstract : Introduction: CHP, the major differential diagnosis for IPF, has varied radiological features that can confound CT agreement in up to a third of cases of fibrotic interstitial lung disease presenting to multidisciplinary panels. Given that the pathological basis of CHP incorporates diffuse bronchiolitic abnormalities, we hypothesised that differences in small airway dysfunction and resultant air-trapping might help refine a multi-domain approach to distinguishing CHP from IPF. Methods: Analysis of lung function records of individuals with multidisciplinary diagnoses of CHP and IPF (n=118 in each group) with matched disease severity (% predicted FVC: 69.3±21.9 vs. 73.8±16.2 respectively, p=n/s and% predicted TLco: 39.2±14.8 vs 39.9±13.1 respectively, p=n/s) at the Royal Brompton Hospital was undertaken. Indices relating to airflow, dynamic and static lung volumes were compared. Data were analysed using parametric tests following testing for normal distribution and expressed as mean ±SD. A p-value<0.05 was considered statistically significant. Results: Compared to patients with IPF, the CHP cohort was characterised by considerably worse small airway impairment as denoted by significantly lower%-predicted values of mid-expiratory flow (MEF25/50/75 ; p<0.0001), forced expiratory volume at 3 s (FEV3 ; p<0.05), volumic inspiratory and expiratory airway conductance (GAW ) as well as resistance (RAW ) (p<0.0001). In contrast, indicators of greater air-trapping including residual volume/RV and the RV/TLC ratio were increased in CHP (p<0.0001 and p<0.0001 respectively) while contraction of total lung capacity occurred to a lesser extent in this group (p=0.01). The gas transfer coefficient/Kco was lower in CHP than in IPF (p=0.01). Conclusion: Although both diseases result in restrictive pulmonary physiology, patients with CHP have demonstrably worse small airway function than those with IPF, as evaluated by a range of flow and volume determinants. Consequent upon these changes, a higher degree of air-trapping is evident in the CHP cohort. The radiologic correlates of such observations, namely bronchocentric fibrosis and lobular air-trapping, are widely recognised in CHP. In future, integration of a more disease-specific physiologic profile with detailed assessment of disease behaviour, volumetric radiology and dynamic small airway tests may enhance the accuracy of diagnosing CHP.